Quantum cosmology - Shtanov, Yu.V. (Вопросы атомной науки и техники, 2013)
We discuss quantum-cosmological approach to the problem of initial singularity and origin of our universe, starting with the pioneer idea of quantum creation of the universe put forward by P.I. Fomin.